St. Hyacinth’s Church in Warsaw: The Problem of References to Gothic in Polish Architecture of the 17th Century - Vaniushin, Artem S. (Actual Problems of Theory and History of Art, 2018)
The article is dedicated to the archaizing tendencies in Polish architecture of the 17th century. On the one hand, such tendencies can be considered as a result of the persistence of Late-Gothic tradition in provincial architecture. On the other hand, they can be interpreted as a conscious reference to the architectural heritage of the 13th-16th centuries, which is determined by various factors. Such references to Gothic are called ‘post-Gothic’ in Polish scientific literature. The Church of St. Hyacinth in Warsaw, built in 1605-1638, is one of the most prominent examples of such a phenomenon. The inclusion of diverse post-Gothic elements in the design of the church, as in other similar cases, was determined by the context of the Counter-Reformation and aimed at attesting the historical nature of the tradition of the Dominican Order.
Keywords: Polish art; Polish architecture; references to Gothic; post-Gothic; Dominicans; Counter-Reformation